EFEKTIVITAS KERJA KARYAWAN: KOMUNIKASI DAN KERJA SAMA TIM PADA RS. CITRA SUNDARI - Rheina Oktiviani; Yulaikah; Djaka Adiwinata (Jurnal Studia Akuntansi dan Bisnis (The Indonesian Journal of Management & Accounting), 2024)
This research aims to determine and test the effect of communication and teamwork on work effectiveness partially and simultaneously. Using quantitative methods. The data source used in the research is a primary source with data collection techniques, namely by distributing questionnaires. The population in this study was 140 people and samples were taken using the Slovin formula so that the total sample was 58 respondents. Data analysis techniques use Validity Test, Reliability Test, Classical Assumption Test, Multiple Linear Regression Test, T Test (Partial), F Test (Simultaneous) and Determination Coefficient (R2). Data management in this research uses the SPSS 21 software. The research results show that partially communication has a positive and significant influence on employee work effectiveness, while teamwork has a positive and significant influence on employee work effectiveness. Simultaneously, communication and teamwork together have a significant effect on employee work effectiveness. The correlation between communication and teamwork has a very strong correlation with a value (R2) of 0.579, while communication and teamwork skills are 57.9% and the remaining 42.1% can be explained by other variables not studied.